Analisis Pengaruh Konteks dan Klien & Koalisi terhadap Kinerja Implementasi Gerakan Literasi Sekolah di Kota Semarang - Lady Marietha Theresa Noge1; Kismartini Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
This study aims to describe the position and role of implementation performance, context and client & coalition in the course of School Literacy Movement Program as well as analyze the effect of policy context and client & coalition on the implementation performance of School Literacy Movement in Semarang City. Method used in this study is quantitative explanatory by collecting data through questionnaires, interviews and docmentation studies. Processing techniques use simple and multiple linear regression data analysis. The results showed that implementation performance, context and client & coalition were quite good according to respondents’ assessments. Partially, context affects implementation performance of School Literacy Movement significantly and positively by 45,1% and client & coalition affect the implementation performance of School Literacy Movement by 49,7%. Simultaneously, policy context and client & coalition affect the implementation performance of School Literacy Movement by 60,4%. In th future, schools need to enrich reading facilities and strengthen collaboration with supporting parties.